OPTIMIZATION OF PHYSICO-CHEMICAL FACTORS AUGMENTING IN VITRO BIOMASS PRODUCTION OF PASTEURELLA MULTOCIDA - N. Sarwar; K. Muhammad; M. Rabbani; M. Younus; M. Sarwar; M. A. Ali; K. Hanif; M. Kamran (Journal of Animal and Plant Sciences, 2013)
Pasteurella multocida causes hemorrhagic septicemia (HS), an economically devastating disease in buffalo and cattle. The disease is controlled effectively through mass scale vaccination of the susceptible animals. For a quality vaccine, biomass production of P. multocida along with its capsule (immunogen) is necessary. Physico-chemical factors such as composition of growth medium, temperature, pH, incubation time and stirring along with aeration affecting its biomass production were evaluated. In Casein yeast sucrose (CYS) broth, there was maximum growth during 18 hours incubation. Optimum conditions for maximum growth (8.2 mg/ml) of the bacterium were 35 to 40°C incubation temperature, 7.0 to 8.0 pH and 500 rpm stirring along with aeration during incubation of 24 hours. It was concluded that growth medium (CSY broth), temperature (35 to 40°C), pH (7.0 to 8.0), stirring (500 rpm) with aeration and incubation time (24 hours) are critical points to achieve high growth density (8.2 mg/ml) of P. multocida that is basic requirement for preparation of its cost effective vaccine.
Keywords: Pasteurella multocida; Biomass production; Critical control points; Immunogen